2011
DOI: 10.1080/00221686.2011.629911
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Manning's equation to 1D non-Darcy flow problems

Abstract: In this paper, the concept of Darcy-Weisbach's friction loss in pipe flows is employed and combined with Manning's widely used formula in openchannel flow problems to obtain a new relation for flow in porous rockfill media. A new formula to determine Manning's roughness coefficient of rockfill materials is presented based on the flow and grain characteristics and validated using new experimental data. The results confirm the applicability of Manning's formula for the hydraulically rough regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…A similar behavior to this is essentially depicted in Figure 3 of Sedghi-Asl et al and Rahimi et al [60]. They suggested that the voids and the angular sediment edges become larger, which leads to an increase in flow resistance.…”
Section: Influence Of Particle Diameter On Friction Factorsupporting
confidence: 74%
“…A similar behavior to this is essentially depicted in Figure 3 of Sedghi-Asl et al and Rahimi et al [60]. They suggested that the voids and the angular sediment edges become larger, which leads to an increase in flow resistance.…”
Section: Influence Of Particle Diameter On Friction Factorsupporting
confidence: 74%
“…These are the nonlinear laminar flow regime (also known as Forchheimer regime or transition flow regime) and the fully turbulent flow regime (Andersen and Burcharth 1995;Lage 1998;Houben 2015). This is done by flow visualization studies in porous media that determined the onset of turbulent flow (e.g., Dybbs and Edwards 1984;Seguin et al 1998), as well as analysis of macroscale flow experiments on packed beds (e.g., Venkataraman and Rao 1998;Sedghi-Asl and Rahimi 2011;Bağci et al 2014). This transition between the different flow regimes in the post-Darcian flow regime is hard to define for natural irregular and graded granular materials such as used in this study (Andersen and Burcharth 1995).…”
Section: Discussionmentioning
confidence: 99%
“…where g [m/s 2 ] is the acceleration due to gravity, d [m] is the characteristic pore length by means of the particle diameter, v [m 2 /s] is the kinematic viscosity of the fluid, n [−] is the porosity, A is the Ergun constant that equals 150 and B is the Ergun constant that equals 1.75 (Ergun 1952). Many variations on the Ergun relation for different kinds of porous media and flow regimes are given in the literature (e.g., Engelund 1953;Irmay 1964;Mac-Donald et al 1979;Du Plessis 1994;Sedghi-Asl and Rahimi 2011;Erdim et al 2015;Guo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental data on (post-Darcy) nonlinear flow in porous media are available for coarser porous media, such as coarse sands, gravels and glass beads (Sidiropoulou et al 2007;Moutsopoulos et al 2009;Sedghi-Asl and Rahimi 2011;Huang et al 2013;Bagci et al 2014;Salahi et al (2015); Sedghi-Asl et al 2014;Li et al 2017). A relatively small amount of experimental data is available for finer unconsolidated sandy porous media.…”
mentioning
confidence: 99%